2014
DOI: 10.3846/1648715x.2014.971088
|View full text |Cite
|
Sign up to set email alerts
|

Determining Appropriate Government Guarantees for Concession Contract: Lessons Learned From 10 PPP Projects in China

Abstract: ABSTRACT. Governments worldwide are keen to encourage PPP schemes, however PPP is not a foolproof business. Many local governments and private investors have suffered severe or trying experiences. In this research, 10 case studies were conducted to identify the obstacles and difficulties for successful implementation of PPP projects from the perspective of government guarantees. These PPP projects include two water supply plants, two sewage treatment plants, two power supply plants, two highway projects, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…In recent years, an increased interest in developing countries regarding cooperation among public and private sectors to develop and operate infrastructure projects such as transportation, water, electrical power, telecommunications and sports facilities in particular has been observed (Heravi, Hajihosseini 2011;Li, Zou 2011;Tserng et al 2014;Xu et al 2014). Public-private partnership (PPP) projects are normally implemented to secure public projects through private investment (Xu et al 2010); yet, serious shortages of experience, a paucity of relevant studies and complex PPP agreements in developing countries can be noticed (Heravi, Hajihosseini 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an increased interest in developing countries regarding cooperation among public and private sectors to develop and operate infrastructure projects such as transportation, water, electrical power, telecommunications and sports facilities in particular has been observed (Heravi, Hajihosseini 2011;Li, Zou 2011;Tserng et al 2014;Xu et al 2014). Public-private partnership (PPP) projects are normally implemented to secure public projects through private investment (Xu et al 2010); yet, serious shortages of experience, a paucity of relevant studies and complex PPP agreements in developing countries can be noticed (Heravi, Hajihosseini 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chileshe and Yirenkyi-Fianko [67] and Ke et al [68] also indicated that change of inflation rate could result in cost overrun so as to affect the financial viability of PPP projects. Furthermore, B1 (Governmental policy support) contributes greatly to the profits, which is the same with in other PPP projects [66]. Although B2 (Interest rate) does not receive high score in questionnaire survey, the result of SEM still highlights it as a sensitive factor for long-term operating a PPP project [53].…”
Section: Measurement Component Of Sem Frameworkmentioning
confidence: 70%
“…Usually, governmental fiscal supports for financing long term infrastructure projects would help reduce the rents of PRH [19,65]. The local governments may play the role of guarantees and provide subsidies in promoting PPP projects in making financing and securing budgets feasible for long term operation, which could bring economic benefits for private sectors to obtain reasonable profits [59,66]. On the other hand, change of inflation rate has been identified as a critical risk factor in PPP projects by many prior studies [67,68].…”
Section: Survey Resultsmentioning
confidence: 99%
“…The influence could be seen in both allocating risks and defining risk allocation in the contract. Taking Beijiao Sewage Treatment Plant for instance (Xu, Yeung and Jiang, 2014), the government shared the operating revenue risk by guaranteeing a minimum amount of water supply, of 70% of the designed water amount. If the actual amount of water supply is lower than 70%, the government will pay the sewage treatment fee at 70% of the designed amount.…”
Section: Risk Allocationmentioning
confidence: 99%
“…If the actual amount of water supply is lower than 70%, the government will pay the sewage treatment fee at 70% of the designed amount. However, the government incentives must be carefully evaluated, as inappropriate guarantees offered by the government are regarded as one of the root causes of PPP projects' failure in China (Xu, Yeung and Jiang, 2014).…”
Section: Risk Allocationmentioning
confidence: 99%